2021
DOI: 10.1182/blood.2020008986
|View full text |Cite
|
Sign up to set email alerts
|

RNF217 regulates iron homeostasis through its E3 ubiquitin ligase activity by modulating ferroportin degradation

Abstract: Ferroportin (FPN), the body's sole iron exporter, is essential for maintaining systemic iron homeostasis. In response to either increased iron or inflammation, hepatocyte-secreted hepcidin binds to FPN, inducing its internalization and subsequent degradation. However, the E3 ubiquitin ligase that underlies FPN degradation has not been identified. Here, we report the identification and characterization of a novel mechanism involving the RNF217-mediated degradation of FPN. A combination of two different E3 scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 73 publications
(45 reference statements)
0
34
1
1
Order By: Relevance
“…Ferroportin is the only known iron exporter in vertebrate cells, and cardiac iron overload, impaired heart function and a shortened lifespan have been observed in mice with early cardiomyocyte-specific deletion of the gene encoding ferroportin ( Fpn ) 29 , 30 . Hepcidin, a peptide hormone primarily synthesized in the liver, inhibits ferroportin via E3 ubiquitin protein ligase RNF217-mediated ubiquitination in the gut and spleen, which regulates iron absorption and iron recycling, respectively 31 , 32 . Genetic hepcidin deficiency causes the most severe form of systemic iron overload in both mice and humans 33 , 34 .…”
Section: Molecular and Metabolic Drivers Of Ferroptosismentioning
confidence: 99%
“…Ferroportin is the only known iron exporter in vertebrate cells, and cardiac iron overload, impaired heart function and a shortened lifespan have been observed in mice with early cardiomyocyte-specific deletion of the gene encoding ferroportin ( Fpn ) 29 , 30 . Hepcidin, a peptide hormone primarily synthesized in the liver, inhibits ferroportin via E3 ubiquitin protein ligase RNF217-mediated ubiquitination in the gut and spleen, which regulates iron absorption and iron recycling, respectively 31 , 32 . Genetic hepcidin deficiency causes the most severe form of systemic iron overload in both mice and humans 33 , 34 .…”
Section: Molecular and Metabolic Drivers Of Ferroptosismentioning
confidence: 99%
“…Hepcidin inhibits cellular iron efflux by binding to and inducing the degradation of FPN. RNF217 was identified as a novel E3 ubiquitin ligase and was shown to play a role in mediating the degradation of FPN [ 30 ]. Notably, we previously showed that iron overload can directly induce ferroptosis in a variety of organs, including the liver and heart [ 14 , 26 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been displayed that FPN1 is able to be phosphorylated and ubiquitinated (De Domenico et al, 2007); however, the corresponding E3 ubiquitin ligases and DUBs remain largely unknown. A recent study has shown that RNF217 mediates the ubiquitination and subsequent degradation of FPN1 (Jiang et al, 2021).…”
Section: Ubiquitination In Iron Metabolismmentioning
confidence: 99%